THE IMPACT OF MARKETING AGILITY AND CUSTOMER EXPERIENCE MANAGEMENT IN MARKETING ENTREPRENEURSHIP: AN APPLIED STUDY IN A SAMPLE OF IRAQI INDUSTRIAL COMPANIES - Ahmed Kadem Abed AL Aboudy (Scholars Digest Publishing, 2025)
The current research collected and studied the three variables that the previous researches are not gathered together. The research aims to demonstrate the impact of marketing agility and customer experience management in marketing entrepreneurship in order to reach the means that help in creating and maintaining demand, suitability, reputation and competitive advantage, and it lays the foundation for how businesses reach their current and targeted customers. The research was applied to a sample of individuals working in Iraqi industrial companies, including administrators, accountants, and auditors. The focus was on companies specialized in the electrical industry, which are the General Company for Electrical Industries, Al-Waziriya Branch, and the Diyala Branch. A questionnaire form was designed to be consistent with the objectives and hypothesis of the research. (118) questionnaire forms were distributed, and (115) forms were retrieved that were capable of statistical analysis, i.e., a percentage of (97.4%). The research reached a set of conclusions, the most important of which was that there is a relationship between marketing agility and marketing entrepreneurship, as many organizations are working to implement process automation in all fields in order to help improve their marketing performance. The research recommends the need to develop and define standards to evaluate the marketing agility practices and marketing entrepreneurship.
Keywords: Marketing agility, marketing entrepreneurship, customer experience management.